Salivary gland carcinomas in children and adolescents: The Italian TREP project experience. Issue 11 (17th August 2014) - Chiaravalli, Stefano; Guzzo, Marco; Bisogno, Gianni; De Pasquale, Maria Debora; Migliorati, Roberta; De Leonardis, Francesco; Collini, Paola; Casanova, Michela; Cecchetto, Giovanni; Ferrari, Andrea
<x xml:space="preserve">Abstract</x> Background Salivary gland carcinomas are extremely rare in pediatric age. We report the clinical features of a series of children/adolescents with salivary gland carcinomas prospectively registered in the Italian TREP (Rare Tumors in Pediatric Age) project. Procedures Diagnostic/therapeutic guidelines were developed and shared among Italian pediatric oncology/surgical centers. Results Seventeen patients were registered between 2000 and 2012, representing 19% of the cases expected to be seen based on epidemiological data. Tumors arose mainly in the parotid gland (14 cases). In most cases they were low‐grade tumors (14 cases), often with a favorable clinical presentation, and low‐stage disease. All patients underwent surgical resection, achieving histologically free margins in 9/17 cases. Thirteen of the 14 patients with parotid gland tumors had parotidectomy (10 total, 3 superficial), while one had a tumorectomy. Postoperative facial nerve lesions were reported in two cases. Adjuvant radiotherapy was given to 6 patients. The overall prognosis was good: only one patient with a huge high‐grade tumor experienced disease progression and died of the disease. The other 16 patients were alive in first continuous remission 1–8 years after diagnosis. In 4/17 cases, the salivary gland carcinoma was a second tumor occurring 6–9 years after another primary cancer. Conclusions This is the first reported prospective national cooperative series of pediatric salivary gland carcinoma patients. Compliance with the TREP recommendations was high. These tumors are rarely managed by pediatric oncologists/surgeons. A broader international cooperation and better networking with otolaryngologists and head‐neck surgeons expert on adult salivary gland carcinomas would be advisable. Pediatr Blood Cancer 2014;61:1961–1968. © 2014 Wiley Periodicals, Inc.